Menu development for portable Qibla finder using GPS - Kamaruddin, Nurulhuda (2007)
Portable Qibla finder using GPS is a device specifically to show the user the location of Qibla, which Muslims needs in order to perform prayers. Normally, people use a compass to determine the Qibla direction but in today developing era, there are so many thinkable solutions. This project intention is to design a portable Qibla finder using GPS. The menu development of the portable Qibla finder using GPS depends on the source code appended into the PIC16F877A microcontroller that acts as the brain of the whole systems which consists of 5 modules which are the power supply module (5V DC power supply for operation), GPS module, controller unit module (PIC16F877A to store command), GLCD module (displaying text and graphics) and also the input module (tack switch for the navigation purposes). MPLAB IDE and PROTEUS VSM is used for assembling and debugging purposes. This project consists of 5 chapters by which each chapters begins with the introduction, followed by interpretation that associate with each chapter's scope. Chapter 1 exhibits the overview of the project that includes the problem argument, significance of the project, the objectives of the project and a glimpse of the scope of work. Chapter 2 cover the literature review of the project. All the components and softwares used in the project such as the PIC 16F877A, graphic LCD, IC78L05, IC7660, MPLAB SOFTWARE and Proteus are explicate in details. Chapter 3 is focusing on the methodology, by means the software design in constructing the source code for the menu. Chapter 4 emphasis the results, together with discussion for each results obtained throughout the completion of this project. The final chapter, chapter 5 will consists the conclusion and the future development of the project.